Analisis Termal Lemari Es dengan Variasi Jenis dan Ketebalan Isolasi di Iklim Tropis - Muhammad Azril Rahmaditya; Boni Sena; Farradina Choria Suci; Ihsan naufal firdaus; Faishal Dzaky Al Hakim; Dimas Bahrudin; Ridwan Abdul Hakim; Muhamad Ilham Saputra (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2026)
Cutting speed is a crucial parameter in the turning process that significantly affects the final quality of the workpiece surface. This study aims to evaluate the impact of cutting speed variations on the surface roughness level of AISI 1018 steel. The machining process was carried out using a chisel with a tip radius of 1.2mm, and the cutting speed was varied at three levels, namely 42m/min, 66m/min, and 105m/min. Surface roughness measurements were carried out using a Surface Roughness Tester. The experimental results showed that increasing cutting speed tended to decrease surface roughness. The lowest roughness value of 2.224 μm was obtained at a cutting speed of 105 m/min. This phenomenon occurs because, at higher cutting speeds, cutting forces and vibrations are reduced, making the machining process more stable and producing better surface quality. This study shows that cutting parameters play an important role in optimizing the final results of conventional turning processes.